2020
DOI: 10.1055/s-0039-3401811
|View full text |Cite
|
Sign up to set email alerts
|

Average Tibial Plateau Angle of 3,922 Stifles Undergoing Surgical Stabilization for Cranial Cruciate Ligament Rupture

Abstract: Objective The aim of this study was to report the average tibial plateau angle (TPA) from a large sample of dogs and to determine if breed or gonadectomy had a significant association with abnormal TPA. Study Design This was a retrospective case study. Materials and Methods Medical records from 2006 to 2015 were reviewed for dogs that were diagnosed with cranial cruciate ligament (CrCL) rupture and underwent dynamic surgical stabilization. Signalment, examination findings, preoperative TPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This delay in skeletal maturity might be associated with increased opportunity for errors in skeletal modeling that render the cranial cruciate ligament more susceptible to rupture. Two studies have demonstrated that the occurrence of increased tibial plateau angle (TPA), a phenotype that may be associated with increased risk for CCL rupture, is increased by gonad removal 41 , 42 . Although reported differences between TPA in cases and non-cases are inconsistent 32 , 34 , 35 , 43 47 , the finding that increased TPA may be a gonad-sensitive phenotype raises the possibility that other morphometric variables, such as intercondylar notch width 48 or femoral anteversion angle 31 , may also be sensitive to early endocrine disruption.…”
Section: Discussionmentioning
confidence: 99%
“…This delay in skeletal maturity might be associated with increased opportunity for errors in skeletal modeling that render the cranial cruciate ligament more susceptible to rupture. Two studies have demonstrated that the occurrence of increased tibial plateau angle (TPA), a phenotype that may be associated with increased risk for CCL rupture, is increased by gonad removal 41 , 42 . Although reported differences between TPA in cases and non-cases are inconsistent 32 , 34 , 35 , 43 47 , the finding that increased TPA may be a gonad-sensitive phenotype raises the possibility that other morphometric variables, such as intercondylar notch width 48 or femoral anteversion angle 31 , may also be sensitive to early endocrine disruption.…”
Section: Discussionmentioning
confidence: 99%